Parental Feeding Styles Related to the Stunting in Sleman, Indonesia - Bella, Nur Aisyah; Fauzia, Faurina Risca; Mahfida, Silvi Lailatul (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
The study aimed to determine the correlation between parental feeding style and stunting in toddlers. This study was an observational method with a cross-sectional design. The population of this study were all mothers of toddlers who were in the Minggir Puskesmas (Public Health Center) working area. The sample size in this study was 114 mothers of toddlers, and the sample was chosen using the cluster random sampling technique. Determination of parenting style variables based on demandingness and responsiveness scores. There are four categories of parental feeding styles, namely democratic, authoritarian, permissive, and neglect parenting. Anthropometric measurements of toddlers were carried out directly, and interviews using the parental feeding style questionnaire that had been tested for validation and reliability. That the data was analyzed with Fisher’s Exact test. The Fisher’s Exact test revealed that there was a correlation between parental feeding styles approaches to the stunting incidence with the value of p=0.000 (p<0.05). The parental feeding style that mostly applied to cause stunting is the neglect-feeding style (8.8%). Parents should further improve their parenting patterns by always paying attention to food intake, especially the amount, frequency of feeding, and type of food.